The Urgency of Educational Media in Learning Islamic Religious Education - Ibnu Rusydi (Penerbit Hellow Pustaka, 2023)
The purpose of writing this paper is to examine the urgency of educational tools and media in learning Islamic Religious Education, their functions, varieties, and criteria for their use. Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education through formal education, basic education and secondary education. In carrying out tasks related to the implementation of learning the teacher should master the learning media. Learning media is very important to be understood and used by Islamic religious teachers in carrying out their learning in order to achieve the learning objectives that have been set. More specifically, the notion of media in the teaching and learning process tends to be interpreted as graphic, photographic, or electronic tools for capturing, processing, and reconstructing visual or verbal information. Educational or learning tools and media are one of the components of the learning system that interact and interrelate with other components in the learning process, so that the educational or learning objectives that have been set can be achieved effectively and efficiently.